VARIOUS DECORATIVE OF KALA AS AN ORNAMENTAL ART WORKS - Sumadi Sumadi (Institut Seni Indonesia Surakarta, 2011)
Various kind of Kala is one of temple ornament, that are patterned face of the giant's head Kala at every Hindu Indonesia Java temple entrances. Kala’s ornament is come from India named Kirtimukha. It has beautiful form, strange, unique and mythic, it also is noted by many parties. Its presence raises contradiction. Giant Kirtimukha was born out of anger of Siva, which raised a fire of anger from between her eyebrows. Kirtimukha that has very big power called Mahakala, with grim face, grinning mouth and sharp fang, killer and cannibal, was assigned to keep the palace/temple. Giant Kirtimukha or Mahakala is ornament of palace doors in India deva and Java temple, and then spreads to the East Java named Banaspati, to Bali named Boma, the mask, Betara Kala, Barong, Gupala, Bhutakala and others. Frequently, the word Kala is also associated with time and the sun. Each Kala in separated region has its own form and function. Heaven Palace buildings architect named Wisvakarma. Kala as temple ornament in Dieng is classical style built on (± 600-900), in Plaosan Lor is middle classical style built on (± 900-1250 AD), in Panataran temple is late classical style built on (± 1250-1400 AD ). Form and function changes in classical style Kala were done in anthropomorphich, metamorphosis, deformative by creative and innovative artist in each period. Period of Hindu artist produce classical Kala ornament as enterance guard on temple or and the like. Period of Islam produces Batara Kala and Gunungan Wayang Kulit Purwa and others.The change of the political, religious and authorities in various regions, is a major cause of changes in form and function of Kala. In a classic Indonesian Hindu temple, Middle and modern period Kala have different name and form, but his function still as an ornamental and security guard of its owner. Modern period produce new type of reliefs and paintings for building wall and many others. Kala ornament is created by creative and innovative artist ranging from design, preparation of materials/equipment and the forming, till producing giant pattern art works or mask.